2021
DOI: 10.1002/cti2.1335
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral injection of caerin 1.1 and 1.9 peptides increases the efficacy of vaccinated TC‐1 tumor‐bearing mice with PD‐1 blockade by modulating macrophage heterogeneity and the activation of CD8+ T cells in the tumor microenvironment

Abstract: Objectives Developing a vaccine formula that alters the tumor‐infiltrating lymphocytes to be more immune active against a tumor is key to the improvement of clinical responses to immunotherapy. Here, we demonstrate that, in conjunction with E7 antigen‐specific immunotherapy, and IL‐10 and PD‐1 blockade, intratumoral administration of caerin 1.1/1.9 peptides improves TC‐1 tumor microenvironment (TME) to be more immune active than injection of a control peptide. Methods W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 105 publications
1
36
0
Order By: Relevance
“…Isolated from the epidermal secretion of Australian amphibians, Litoria genus , caerin 1.1 and 1.9 peptides were found to significantly inhibit the proliferation of TC-1 ( 20 , 21 ) and HeLa cells ( 22 ) at the concentrations non-toxic to typical cells. They appeared to stimulate the signalling of TNFα-mediated apoptosis and activate the TCR pathway in HeLa cells ( 22 , 23 ). Caerin 1.1 and 1.9 largely inhibited the growth of TC-1 tumour in mice, and the inhibition required an intact adaptive immune system; in addition, the treatment prolonged the survival time of vaccinated and PD-1 blocked TC-1 tumour-bearing mice significantly ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Isolated from the epidermal secretion of Australian amphibians, Litoria genus , caerin 1.1 and 1.9 peptides were found to significantly inhibit the proliferation of TC-1 ( 20 , 21 ) and HeLa cells ( 22 ) at the concentrations non-toxic to typical cells. They appeared to stimulate the signalling of TNFα-mediated apoptosis and activate the TCR pathway in HeLa cells ( 22 , 23 ). Caerin 1.1 and 1.9 largely inhibited the growth of TC-1 tumour in mice, and the inhibition required an intact adaptive immune system; in addition, the treatment prolonged the survival time of vaccinated and PD-1 blocked TC-1 tumour-bearing mice significantly ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…The antiproliferative activity of caerin 1.1 and 1.9 against HeLa cells in vitro was investigated, which found that the TNF-a-dependent apoptosis signals were stimulated by the caerin peptides (22). In a recent study, we have shown that intratumoral injection of the caerin 1.1/1.9 mixture significantly prolonged the survival time of TC-1 tumour-bearing mice that were immunised with an HPV16 E7 peptide-based vaccine along with IL-10 and PD-1 blockade (23). The TME was largely altered to a higher immune activation level, possibly with Stat1 as a key modulator, which synergistically functions with the activated NF-kB pathway to induce more iNOS and triggers the recruitment of T cells.…”
Section: Discussionmentioning
confidence: 99%
“…CD4 + CD8 + T cells had the lowest number of cells, with the marker genes such as Cd226, Klrg1 and Cxcr6. Fibroblast (cluster 6; Nusap1, Top2a, Pclaf and Mki67) (28), adipogenic stem and precursor cells (ASPCs) (cluster 11; Col11a1, Plpp3, Col6a1 and Gas1) (23,29), basal cells (cluster 12; Ccnb2, Cdkn3, Hmmr and Birc5) (30) and osteoclast (Cluster 17; Oscar, Ctsk and Mmp9) (31) were detected as possible contaminants (also see Supplementary Data 2).…”
Section: Single-cell Rna-seq Revealed Complex Heterogeneity Of Non-macrophage Cells In the Tmementioning
confidence: 99%
See 2 more Smart Citations